2022
DOI: 10.17645/si.v10i2.5009
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Covid‐19 Global Health Pandemic in Early Childhood Education Within Four Countries

Abstract: The recent Covid‐19 global health pandemic has negatively affected the political and economic development of communities around the world. This article shares the lessons from our multi‐country project Safe, Inclusive Participative Pedagogy: Improving Early Childhood Education in Fragile Contexts (UKRI GCRF) on how children in communities in Brazil, Eswatini, South Africa, and Scotland have experienced the effects of the pandemic. This article benefits from having co‐authors from various countries, bringing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…What the articles in this thematic issue of Social Inclusion suggest is that uniform, "one-size-fits-all" measures such as those taken by various governments across the globe might significantly undermine commitments towards children's and young adults' rights, with the subtlest of all problems being that there is no recognition of their abilities to contribute to discussions on the pandemic or make meaningful decisions about their lives (see McNair et al, 2022), something that poses a new dilemma concerning the very core of our purportedly democratic societies. In that sense, what the authors acknowledge is a retrenchment of policies concerning children's and young adults' rights globally, something that seems to bring us back to a previous stage of human development.…”
Section: Discussionmentioning
confidence: 99%
“…What the articles in this thematic issue of Social Inclusion suggest is that uniform, "one-size-fits-all" measures such as those taken by various governments across the globe might significantly undermine commitments towards children's and young adults' rights, with the subtlest of all problems being that there is no recognition of their abilities to contribute to discussions on the pandemic or make meaningful decisions about their lives (see McNair et al, 2022), something that poses a new dilemma concerning the very core of our purportedly democratic societies. In that sense, what the authors acknowledge is a retrenchment of policies concerning children's and young adults' rights globally, something that seems to bring us back to a previous stage of human development.…”
Section: Discussionmentioning
confidence: 99%
“…When the first wave of the Covid-19 pandemic spread and societies locked down, education in many countries moved online. As McNair et al (2022) discuss in this volume, this reality immediately highlighted inconsistencies in access to education as governments and other stakeholders explored different ways to enable young people to participate in remote learning. In a comparative study that included Brazil, Eswatini, South Africa, and Scotland, the authors found that the pandemic was the catalyst for eroding or even ignoring children's rights and that violence and poverty threatened the protection of their basic rights, which goes against the UN Convention of the Rights of the Child.…”
Section: From Pandemic Fixing To Pandemic Learningmentioning
confidence: 99%
“…However, other contexts provide respite from an approach to online learning that, at best, could be described as troubleshooting. In their article, McNair et al (2022) argue that, even though the pandemic "spotlighted'' inequalities that already existed, schools and teachers were quick to identify and implement innovative practices to reduce the immediate gaps. Ebubedike et al (2022) highlight how a well-tested approach, namely education delivered by radio school in local languages in Northern Nigeria, has proved successful in terms of uptake.…”
Section: From Pandemic Fixing To Pandemic Learningmentioning
confidence: 99%
“…With societal trends, education systems are influenced, while also having the power to affect them [11]. Apart from tumultuous technological, social, economic, and political events that have affected schools on a global scale [9,[12][13][14][15][16], an international staffing crisis in teaching and school leadership now pertains [17] and is likely to become worse because of decreasing rates of teacher recruitment and increases in teacher turnover [18,19]. Globally, as attempts to tackle a rapidly diversifying population [20][21][22], schools must respond to rapid and significant changes to remain relevant for the achievement of societal goals such as inclusion [23,24].…”
Section: Introductionmentioning
confidence: 99%